2018
DOI: 10.14814/phy2.13816
|View full text |Cite
|
Sign up to set email alerts
|

Does competitive swimming affect lung growth?

Abstract: Whether the large lungs of swimmers result from intensive training or genetic endowment has been widely debated. Given that peak lung growth velocities occur during puberty, this study examined if competitive swimming during puberty affected lung growth. Eleven‐ to fourteen‐year‐old healthy female competitive swimmers and controls were assessed before (PRE) and after (POST) one swimming season (7.4 ± 0.5 months). Pulmonary function testing included lung volumes, spirometry, diffusion capacity (DL , CO), and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Other authors suggest that the lungs of competitive swimmers are characterized by higher lung capacity [18] and diffusion capacities [19,20] in comparison with a healthy control group. Meanwhile, Bovard’s research (2018) results show that competitive swim training does not influence the development of lung size or function [21]. Also, in some studies, it has been shown that IMT benefits were the result of a dose-dependent effect of swim training [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors suggest that the lungs of competitive swimmers are characterized by higher lung capacity [18] and diffusion capacities [19,20] in comparison with a healthy control group. Meanwhile, Bovard’s research (2018) results show that competitive swim training does not influence the development of lung size or function [21]. Also, in some studies, it has been shown that IMT benefits were the result of a dose-dependent effect of swim training [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…73 Swimmers had a greater total lung capacity and peak expiratory flow rate than controls 74 but these parameters did not improve significantly after the training season. Therefore, 75 the study suggested that competitive swimming did not affect lung growth during 76 puberty and that large lungs of swimmers are inherent rather than induced [19]. 77 So, not only is there an ongoing discussion about the adaptive possibilities of the 78 respiratory organ, but it also remains unclear whether an increased respiratory volume 79 would actually be achieved by wider alveoli or an increased number of alveoli.…”
mentioning
confidence: 99%
“…Swimmers had a greater total lung capacity and peak expiratory flow rate than controls but these parameters did not improve significantly after the training season. Therefore, the study suggested that competitive swimming did not affect lung growth during puberty and that large lungs of swimmers are inherent rather than induced [19].…”
Section: Introductionmentioning
confidence: 86%